VALIDASI KLINIS GENERAL HEALTH QUESTIONNAIRE-12 SEBAGAI INSTRUMEN SKRINING DEPRESI DI PUSKESMAS - , Ratri Nurwanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Researches and literatures showed that prevalence of depression, undetected and untreated case of depression in primary health care were high. The use of screening instrument is one of the methods that can improve the detection of depression among primary health care patients. General Health Questionnaire â 12 (GHQ-12) is one of the screening instruments that has been adapted and widely used in many countries and showed satisfactory results in screening depression. Therefore, this study aimed to validate the GHQ-12 as a screening instrument of depression in primary health care in Indonesia, Puskesmas. This study used clinical diagnosis made by psychologist with clinical interview guide, SCID-I, as the gold standard.There were 25 clinical psychologists and 25 nurses from 25 Puskesmas in Sleman, Yogyakarta, involved in this study. Results showed that GHQ-12 had good diagnostic quality. Sensitivity, ability to detect positive patients who actually experienced a depressive disorder, was 77% (GHQ & Likert) or 81% (CGHQ). Specificity, able to detect negative patients who did not experience depression, was 62% (GHQ), 61% (Likert) or 63% (CGHQ), AUC value, a reflection of how good the test is at distinguished between patients with disease and those without disease, was 79% (GHQ dan CGHQ) 78% (Likert). LR+, probability of an individual with disease having a positive test, was 2 dan LR-, probability of individual with disease having a negative test, was 0.3. Results also showed acceptable reliability, 0.87 and criterion validity analysis showed that GHQ-12 scores significantly correlated with depression symptoms (p < 0.05), rxy = 0.649 for GHQ scoring method, rxy = 0.579 for CGHQ scoring method, rxy = 0.635 for Likert scoring method.